2016
DOI: 10.12952/journal.elementa.000137
|View full text |Cite
|
Sign up to set email alerts
|

Possible malfunction in widely used methane sampler deserves attention but poses limited implications for supply chain emission estimates

Abstract: Estimates of methane emissions from natural gas production sites in the United States based on recent studies have been questioned due to possible malfunction of the Bacharach Hi Flow ® Sampler (BHFS), the primary measurement instrument used for two out of five source types examined in those studies (equipment leaks and chemical injection pumps). Without assessing whether the BHFS malfunction occurred in those studies, we constrain the possible underestimation of emissions associated with the BHFS-based result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The validity of the study by Allen et al . [] is still an ongoing point of contention [ Alvarez et al ., ]. Given the current low cost of natural gas, a purely economic driver to reduce the atmospheric release of CH 4 by leakage does not exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The validity of the study by Allen et al . [] is still an ongoing point of contention [ Alvarez et al ., ]. Given the current low cost of natural gas, a purely economic driver to reduce the atmospheric release of CH 4 by leakage does not exist.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Howard [2015a] and Howarth [2015] have argued that Allen et al [2013] might have underestimated CH 4 emissions and hence obtained an erroneously low CH 4 leakage rate. The validity of the study by Allen et al [2013] is still an ongoing point of contention [Alvarez et al, 2016]. Given the current low cost of natural gas, a purely economic driver to reduce the atmospheric release of CH 4 by leakage does not exist.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, a recent examination by Alvarez et al suggested that sensor issues may be a part of discrepancies, but that operator practices and general lack of complete data sets could also lead to discrepancies. 31 Therefore, we used data from Allen et al to compare with our emissions. 8…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, Howard (2015a) and Howarth (2015) have argued that Allen et al (2013) might have underestimated CH 4 emissions and hence obtained an erroneously low CH 4 emission rate. The validity of the study by Allen et al (2013) is still an ongoing point of contention (Alvarez et al, 2016(Alvarez et al, , 2018Guglielmi, 2018). It is noteworthy that there is considerable temporal variability in CH 4 emission rates in shale gas production regions, which could lead to variability in these estimates (Lavoie et al, 2017).…”
Section: Discussionmentioning
confidence: 98%